A Case Report of Venoarterial ECMO as Salvage Therapy for Prolonged Cardiac Arrest Following Post-Reperfusion Intracardiac Thrombosis During Orthotopic Liver Transplantation. (March 2021) - Romano, Diana N.; Smith, Natalie K.; Itagaki, Shinobu; Bekki, Yuki; Gunasekaran, Ganesh; Zerillo, Jeron
In this report we describe the use of intraoperative venoarterial ECMO as salvage therapy in a unique case of post-reperfusion intracardiac thrombosis during liver transplantation with prolonged ACLS and coagulopathy. The limited literature on intraoperative ECMO as salvage therapy in liver transplantation is reviewed.